Being All Things to All Customers: Building Reputation in an Institutionalized Field. (9th December 2013) - Wæraas, Arild; Sataøen, Hogne L.
<x xml:space="preserve">Abstract</x> This paper seeks to draw empirical attention to the relationship between legitimacy and reputation in institutionalized fields. Norwegian hospitals find themselves in a strongly institutionalized field and do not want to differentiate from each other, despite seeking a favorable reputation. In order to acquire insights into the conditions that prompt organizations to reject differentiation, we carried out qualitative interviews with the hospitals' communication directors. Three sets of justifications for not differentiating emerged from an inductive analysis of these interviews. Differentiation is not adapted to the universalistic needs of the hospitals, not in accordance with solidarity norms, and not a pragmatic solution. The analysis suggests that the hospitals face a trade‐off between the contradictory demands of similarity and difference and hence legitimacy and reputation: They renounce the advantage of a unique reputation (i.e. competitive advantage) in order to retain the benefits of conformity (i.e. legitimacy). Implications of these findings for our understanding of the relative salience of legitimacy and reputation and the dynamics between them are discussed.